Praktik Textual Poaching dan Perebutan Otoritas Narasi Pada Akun Instagram @theunitedstrand - Ganjar Ndaru Aji (Jayapangus Press, 2026)
Digital media enables sports fans to challenge official club narratives; however, studies exploring the use of the biological body as a medium for satire remain limited. This research aims to examine how the body transforms into a visual metric of a club's failure and how this practice triggers contested authorship between fans and professional athletes in the digital space, focusing on the viral case of the Instagram account @theunitedstrand. This study employs a qualitative netnographic approach utilizing visual and comment interaction analysis. The concepts of textual poaching by Henry Jenkins and affective publics by Zizi Papacharissi are used as theoretical lenses. The study reveals three key findings: (1) fans engage in textual poaching by reappropriating official match result narratives into a satirical bodily performance, turning their hair into a